Survey Purchasing Power Equity i Survey Purchasing Power Equity in Iran: The approach of a Bayesian Threshold Auto regression model: Survey Purchasing Power Equity in Iran - Rezaei, Abbas ali; raeisipour, Ali; Zayandehroodi, Mohsen; Jalaee Esfandabadi, Seyyed Abdolmajid (International Journal of Contemporary Economics and Administrative Sciences, 2019)
The main objective of the research is to investigate the purchasing power parity in Iran using a nonlinear Bayesian Threshold model. In this framework, the study of the purchasing power parity in Iran is used to assess the purchasing power in Iran using the currency data of the US dollar, British pound and Japanese one hundred yen, which is related to the period of 2001 - 2016. In the Bayesian method (nonlinear Bayesian Threshold model), the values ​​are not constant, and in other words, it is random, so a distance is defined. The results show that the exchange rate of the US dollar, the British pound and the Japanese one hundred yen has two regimes. The dollar's dollar exchange rate in the low-income regime has moved to a high-ranking regime after reaching the Rials (15010, 12330). The British pound has moved to the top-down regime after reaching the Rials (47180, 20370). Japan's 100-yen exchange rate has moved to the top-down regime after reaching the Rials (31310, 16000). In addition, observations show that the reaction of the yen against the Rials is relatively stronger than the other two currencies (especially in the second regime)